THE CORRELATION BETWEEN WORM INFECTIONS AND NUTRITIONAL STATUS AMONG ELEMENTARY SCHOOL STUDENTS - Liena Sofiana; Erni Gustina; Yuniar Wardani; Suci Musvita Ayu; Aniq Diya Nata Maula (Universitas Ahmad Dahlan, 2019)
Background: Worm disease is an infectious disease that still becomes a public health problem in Indonesia. Worm can cause a decrease in health, nutrition, intelligence and productivity of the sufferers. Worms as parasitic animals do not only take nutrients in the intestines of children, but they also damage the intestinal wall so that they interfere the absorption of these nutrients, consequently, it will impact on the decreasing of one's nutritional status and cause other complex nutritional problems. Moyudan Health Center is a Community Health Center in Moyudan Sub-District Region which has the highest cases of helminthiasis (worm infection). Therefore, this study aims to determine the relationship between helminthiasis infection and nutritional status.Methods: This was an observational analytic study using a cross-sectional approach. The sample of this study were elementary school students in the work area of Moyudan Health Center with samples of 311 respondents. The sampling technique used by multistage random sampling is the selection of samples consisting of the smallest areas of an area. Faecal examination was carried out by using the direct method and nutritional status assessment was carried out by anthropometric method based on the anthropometric index Body Age Index per Age (BMI / U). Data were analyzed by Fisher's test.Results: The results showed that there were 8 respondents (2.57%) who were positively infected by worms, 28 respondents had underweight nutritional status (9.01%), and 54 respondents had a nutritional status of fat (17.36%). The results of the study showed no correlation between helminthiasis infection and nutritional status (p-value = 0.534).Conclusions: There is no relationship between helminthiasis and nutritional status in elementary school students in the Moyudan Community Health Center Working Area in Sleman Regency with a p-value of 0.534 so that it is concluded that helminthiasis infection does not provide any significant contribution to nutritional status even though cases of helminthiasis still occur in elementary school students. Therefore, it needs more attention from parents, schools and health facilities in dealing with worm problems.